ROLE OF RESPONSIBILITY IN EMOTIONAL BURNOUTOF TEACHERS AT INITIAL STAGE OF PROFESSIONALIZATION - S I Kudinov; S S Kudinov; I V Sedova (Peoples' Friendship University of Russia (RUDN University), 2016)
The article presents a comparative analysis of the empirical research results of the formation of burnout symptoms in the teachers with low and high levels of personal responsibility. The sample of respondents was made by teachers with five years' experience of work. At the preliminary stage the peculiarities of situational and personality anxiety, as well as indicators of emotional stability and neuroticism were studied. As a result of the data analysis the teachers with average anxiety and emotional stability were included in the final group of the subjects. The procedure of the respondents selection was motivated by the desire to exclude the respondents, potentially predisposed to intense emotional burnout due to their individual susceptibility to it from the empirical sample.During carrying out the basic research the responsibility indicators were studied at the first stage. According to the hierarchical distribution of the harmonic variables of responsibility the contrasting levels of the manifestation of this property were revealed and characterized. The high level of responsibility manifestation included mainly the positive characteristics responsible for the intensity of the display properties, such as ergicity, sthenicity, internality, socio-centeredness, meaningfulness and productivity. The second group included the respondents in whose hierarchy of variables property manifestation is dominated by the disharmonious components responsible for the weak manifestations of the property: aergicity, asthenicity, externality, ego-centeredness, etc. The selected indicators of responsibility in the both groups differed at a statistically significant level. At the following stage the emotional burnout indicators in each group were analyzed. The study confirmed the put forward hypothesis that the emotional burnout developed more intensively in the teachers with a high level of personal responsibility, rather than that of the respondents with a low level of this personality trait.